2004
DOI: 10.1159/000076718
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemoattractant Protein-1 Promoter –2518 Polymorphism May Have an Influence on Clinical Heterogeneity of Bipolar I Disorder in the Korean Population

Abstract: The aim of this study was to investigate the association between monocyte chemoattractant protein-1 (MCP1) promoter –2518 polymorphism and DSM-IV-based bipolar I disorder (BID) in Korea. Ninety-two patients with BID and 114 healthy controls participated in this study. A polymerase chain reaction-based method was used for genotyping. Genotype and allele distributions in patients with BID were not different from those of the controls, nor were they different according to clinical factors in the patient group. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
2
5
0
Order By: Relevance
“…The CCL2 rs1024611 (À2518 A>G) polymorphism, affecting the transcriptional activity of the distal regulatory region with functional impact on monocyte CCL2 production, has been analysed in four studies. In only one study, genotype and allelic distributions were found to be significantly heterogeneous, with a higher prevalence of the A allele and AA genotype when comparing BD patients with healthy controls in the Turkish population (72,(81)(82)(83). Interestingly, in another example of the value of stratification, the prevalence of the low-producer A allele was found to be higher in manic patients as compared with depressed or mixed episode bipolar patients (82,84), and a higher frequency of the A allele and AA genotype was found in BD patients compared with patients diagnosed with major depressive disorder (81).…”
Section: Modulators Of Clinical Presentationmentioning
confidence: 99%
“…The CCL2 rs1024611 (À2518 A>G) polymorphism, affecting the transcriptional activity of the distal regulatory region with functional impact on monocyte CCL2 production, has been analysed in four studies. In only one study, genotype and allelic distributions were found to be significantly heterogeneous, with a higher prevalence of the A allele and AA genotype when comparing BD patients with healthy controls in the Turkish population (72,(81)(82)(83). Interestingly, in another example of the value of stratification, the prevalence of the low-producer A allele was found to be higher in manic patients as compared with depressed or mixed episode bipolar patients (82,84), and a higher frequency of the A allele and AA genotype was found in BD patients compared with patients diagnosed with major depressive disorder (81).…”
Section: Modulators Of Clinical Presentationmentioning
confidence: 99%
“…At the genomic level, CCL2 was found to be weakly overexpressed in patients with BD in a Nordic genome‐wide association study . cAMP PDE4B , IL6 , IL1 , TNF , EGR3 , CCL2 , and FABP were investigated in gene polymorphism studies.…”
Section: Description Of Genesmentioning
confidence: 99%
“…Three case-control studies revealed that BD patients present a significant association between the uncommon variant with an adenine (A) at position −2581 of the CCL2 gene that is associated with higher production of the chemokine CCL2/MCP-1 (involved in the recruitment of monocytes, memory T cells and dendritic cells into inflammatory sites) under proinflammatory stimulus [3840]. Despite the reported associations between BD and immune-related genes, none of them has been confirmed by meta-analyses including genome-wide association studies [41, 42].…”
Section: Evidence Of Altered Cytokines In Bipolar Disordermentioning
confidence: 99%